Ligation of patent ductus arteriosus in the very low birthweight newborn infant. Issue 4 (April 1978) - Cooke, R W; Gribbin, B; Gunning, A J; Pickering, D
Abstract : Surgical closure of a patent ductus arteriosus was performed in 8 low birthweight infants suffering from cardiorespiratory failure secondary to a large left-to-right shunt. Mortality from the operation was nil, but only 4 (50%) ultimately survived. Earlier intervention may reduce mortality in these high-risk infants.